The Effect of Psychological Capital on Employment Engagement with the Meaning of Work as Mediators on Educational Power Employees, Universitas Mulawarman Rectorate - Tri Sutrisno; Eny Rochaida; Gusti Noorlitaria Achmad; Indra Suyoto Kurniawan (Budapest International Research and Critics University, 2022)
The Rectorate of Universitas Mulawarman acts as the head office in which educational administration and office administration services are carried out. The purpose of this study was to determine and analyze the effect of psychological capital on work engagement with the meaning of work as a mediator for the education staff who served at the Rectorate of Universitas Mulawarman. This research was conducted by census of all civil servants, education staff in 3 work units of the Rectorate of Universitas Mulawarman as many as 104 people. The analytical method used is the Partial Least Square (SmartPLS) approach. The results of the study show that psychological capital has a positive and significant effect on work meaningfulness, and psychological capital also has a positive and significant effect on work engagement and work meaningfulness has a positive and significant positive and significant effect on work engagement, but work meaningfulness cannot be a mediator on the influence of psychological capital on work engagement. The variable of psychological capital affects the meaningfulness of work by 60% and the remaining 40% is influenced by other variables outside of this study, while the variable of meaningfulness of work and psychological capital gives an influence of 83.60% on the work engagement variable and the remaining 16.40% is influenced by other variables outside of this research.